Space Food Experiences: Designing Passenger's Eating Experiences for Future Space Travel Scenarios - Obrist, Marianna; Tu, Yunwen; Yao, Lining; Velasco, Carlos (Frontiers in Computer Science, 2019)
Given the increasing possibilities of short- and long-term space travel to the Moon and Mars, it is essential not only to design nutritious foods but also to make eating an enjoyable experience. To date, though, most research on space food design has emphasized the functional and nutritional aspects of food, and there are no systematic studies that focus on the human experience of eating in space. It is known, however, that food has a multi-dimensional and multisensorial role in societies and that sensory, hedonic, and social features of eating and food design should not be underestimated. Here, we present how research in the field of Human-Computer Interaction (HCI) can provide a user-centered design approach to co-create innovative ideas around the future of food and eating in space, balancing functional and experiential factors. Based on our research and inspired by advances in human-food interaction design, we have developed three design concepts that integrate and tackle the functional, sensorial, emotional, social, and environmental/ atmospheric aspects of “eating experiences in space”. We can particularly capitalize on recent technological advances around digital fabrication, 3D food printing technology, and virtual and augmented reality to enable the design and integration of multisensory eating experiences. We also highlight that in future space travel, the target users will diversify. In relation to such future users, we need to consider not only astronauts (current users, paid to do the job) but also paying customers (non-astronauts) who will be able to book a space holiday to the Moon or Mars. To create the right conditions for space travel and satisfy those users, we need to innovate beyond the initial excitement of designing an “eating like an astronaut” experience. To do so we can draw upon prior HCI research in human-food interaction design and build on insights from food science and multisensory research, particularly research that has shown that the environments in which we eat and drink, and their multisensory components, can be crucial for an enjoyable food experience.